Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Sejarah Lokal pada Materi Kolonialisme di Madrasah Aliyah Se-Kecamatan Stabat - Hartanto, Deni; Veronika, Nabila; Novianti, Yusda (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to develop a Student Worksheet (LKPD) focused on local history, specifically addressing colonialism topics. The objective is to determine the validity and feasibility of the LKPD through evaluations by material and media experts, as well as through limited trials conducted with students from Madrasah Aliyah in Stabat District. This study employs research and development (R&D) methodologies. The developed LKPD underwent validation by two experts: material experts and media experts. The validation results indicated that in the second validation, the material expert assigned a feasibility percentage of 91%, categorized as "Very Valid," while the media expert assigned a percentage of 90%, also categorized as "Very Valid." The trial results were confined to grade XI students, who demonstrated a favorable response with an average score of 87%, categorizing them as "Very Positive." The findings indicate that the LKPD centered on local history concerning colonialism is deemed highly feasible and practical for use in history education at the Madrasah Aliyah level.